Effect of Ankle-Foot Orthotic Devices on Foot Kinematics in Stage II Posterior Tibial Tendon Dysfunction - Neville, Christopher (Foot Ankle Int, 2012)
BACKGROUND: Data are limited on the various orthotic devices available for patients with Stage II posterior tibial tendon dysfunction (PTTD). Foot kinematics observed while walking with an orthotic device are hypothesized to be associated with clinical outcomes and could be used to refine future device designs. METHODS: Fifteen subjects (age, 63.6 ± 6.8 years) with Stage II PTTD walked in the lab under four conditions: (1) shoe only (control condition), (2) shoe with a custom solid AFO (Arizona Co, Mesa, AZ), (3) shoe with a custom articulated AFO (Arizona Co, Mesa, AZ), and (4) shoe with an off-the-shelf AFO (AirLift, DJ Orthopedics). Kinematic data were collected to determine the degree of hindfoot inversion, forefoot plantarflexion (reflective of raising the MLA), and forefoot adduction associated with each condition. RESULTS: The custom articulated device was associated with greater hindfoot inversion compared to the shoe only condition at loading response (p = 0.002), mid-stance (p < 0.001), and terminal stance (p = 0.02). The custom articulated device, custom solid device, and off-the-shelf device were associated with greater forefoot plantarflexion compared to the shoe only condition across all four phases of stance. There were no differences between any of the devices and the shoe condition associated with forefoot adduction. CONCLUSION: The custom devices were associated with greater hindfoot inversion and forefoot plantarflexion compared to walking with only a shoe, while the off-the-shelf device was associated with forefoot plantarflexion but no change in hindfoot motion. None of the devices corrected forefoot abduction compared to the shoe only condition. CLINICAL RELEVANCE: The current biomechanical data may aid in understanding the clinical outcomes seen using these devices as well as provide data to support new designs.